Carbon-based nanomaterials for energy conversion and storage applications in electrochemical catalysis - Zhang, Jia-Nan (Springer series in materials science, 2022)
This book systematically summarizes the advanced development of carbon-based nanomaterials for electrochemical catalysis, and it is comprised of four sections. The first section discusses about the fundamental synthesis, characterization techniques, and catalytic effects on the energy conversion and storage mechanism. The second section elaborately reviews various types of electrocatalytic reactions on carbon-based materials and their performance. The third section focuses on batteries about carbon-based materials with different storage mechanism. And the last one, the following enlightenment in terms of theoretical development and experimental research is provided to the general readers: 1) Precise design and construction of local atomic and electronic structures at the interface of catalysts; 2) Selective activation and directed conversion of carbon-based energy-carrying molecules at the interface; 3) Interaction mechanism and regulation of catalyst solid surface interface properties under environment and external field. This book will be useful for researchers and students who are interested in carbon-based nanomaterials, electrochemical catalysts and energy storage